Decreased peak expiratory flow rate associated with mortality in idiopathic pulmonary fibrosis: A preliminary report. (6th July 2022) - Fujita, Kohei; Ohkubo, Hirotsugu; Nakano, Akiko; Takeda, Norihisa; Fukumitsu, Kensuke; Fukuda, Satoshi; Kanemitsu, Yoshihiro; Uemura, Takehiro; Tajiri, Tomoko; Maeno, Ken; Ito, Yutaka; Oguri, Tetsuya; et al.
Objectives: The peak expiratory flow rate (PEFR) is known to decrease in patients with sarcopenia. However, little is known about the clinical impact of the PEFR in idiopathic pulmonary fibrosis (IPF). This study aimed to confirm whether a decrease in PEFR over 6 months was associated with survival in IPF patients. Methods: Consecutive IPF patients who had been assessed at a single center were retrospectively analyzed. The relative decline in PEFR over 6 months was assessed. Survival analyses were performed by univariate and multivariate Cox proportional hazard models. Results: A total of 61 eligible cases (average age 70 years) were examined, and 21 patients (34.4%) died. The univariate Cox regression analysis showed that the body mass index, baseline % predicted forced vital capacity (FVC), baseline % predicted PEFR, % predicted diffusion capacity for carbon monoxide (DLCO ), relative decline in FVC, and relative decline in PEFR were prognostic factors. On multivariate analyses, relative decline in PEFR (hazard ratio [HR] 1.037, p < .05) and baseline % predicted FVC (HR 0.932, p < .001) were independent prognostic factors, whereas relative decline in FVC was not. Conclusion: A decrease in PEFR after 6 months may predict worse survival in patients with IPF.